2020
DOI: 10.1111/dme.14227
|View full text |Cite
|
Sign up to set email alerts
|

How 25 years of psychosocial research has contributed to a better understanding of the links between depression and diabetes

Abstract: This narrative review of the literature provides a summary and discussion of 25 years of research into the complex links between depression and diabetes. Systematic reviews have shown that depression occurs more frequently in people with type 1 or type 2 diabetes compared with people without diabetes. Currently, it remains unclear whether depression is also more common in people with impaired glucose metabolism or undiagnosed type 2 diabetes compared with people without diabetes. More prospective epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
1
23
0
4
Order By: Relevance
“…Anxiety and depression often coexist and may partly overlap with symptoms of diabetes distress (174). Psychological distress, including mild to major depression, is a risk factor for poor self-care, hyperglycemia, complications, and excess mortality (174)(175)(176). The association between generalized anxiety and suboptimal blood glucose levels is less clear (177,178).…”
Section: Psychosocial Problemsmentioning
confidence: 99%
“…Anxiety and depression often coexist and may partly overlap with symptoms of diabetes distress (174). Psychological distress, including mild to major depression, is a risk factor for poor self-care, hyperglycemia, complications, and excess mortality (174)(175)(176). The association between generalized anxiety and suboptimal blood glucose levels is less clear (177,178).…”
Section: Psychosocial Problemsmentioning
confidence: 99%
“…The mechanisms connecting depression to less favourable outcomes of diabetes are unclear but may be related to biological and behavioural factors (24). Indeed, a meta-analysis of 47 studies showed that depression is associated with less optimal diabetes self-care behaviours (6).…”
Section: Discussionmentioning
confidence: 99%
“…Many in these vulnerable groups already have poor diabetes outcomes [6–8]. Diabetes teams will need to be mindful that the proportion of people with significant psychological needs in their clinic is likely to increase over the coming weeks and months, as is the severity of issues experienced by people with pre‐existing mental ill‐health, and these issues will impact negatively on diabetes outcomes [9]. Awareness of psychological issues, and competency in basic assessment and empathic exploration of issues will become even more essential within diabetes teams.…”
Section: Individual Level Risksmentioning
confidence: 99%